2012
DOI: 10.1161/circulationaha.111.040279
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Left Ventricular Assist Device Support

Abstract: M ore than 5 million Americans are living with heart failure, with an additional 500 000 cases diagnosed each year. 1 Ongoing improvements in patient management will only increase the number of patients surviving to develop severe refractory heart failure (stage D). Approximately 5% to 10% of all heart failure patients are classified as stage D and defined as patients who continue to have symptoms of dyspnea or fatigue at rest despite optimal medical management. 2 Mechanical circulatory support (MCS) is an adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 55 publications
6
81
0
7
Order By: Relevance
“…Several studies 4,6,7) have reported that the exercise therapy based on the patient's condition was the safest and improved his or her exercise capacity and QOL. According to this study, the result showed that an individualized exercise intervention using different parameters should be considered when an exercise prescription was conducted for patients with implanted LVADs to supporting more suitable exercise programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies 4,6,7) have reported that the exercise therapy based on the patient's condition was the safest and improved his or her exercise capacity and QOL. According to this study, the result showed that an individualized exercise intervention using different parameters should be considered when an exercise prescription was conducted for patients with implanted LVADs to supporting more suitable exercise programs.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the depression can be affect to QOL which reflects a person's overall appraisal of their physical and mental states. The MLHFQ was useful as a general survey of the physical and mental states of patients with an implanted LVAD 7) . The MLHFQ of this study increased significantly, but the improvement in score was greater in the second case than in the first case.…”
Section: Discussionmentioning
confidence: 99%
“…2011;86(6):493-500 DT = destination therapy; ICD = implantable cardioverter-defibrillator; LVAD = left ventricular assist device; PM = palliative medicine; QOL = quality of life whelmed with financial and psychosocial issues related to DT [8][9][10][11] and are at risk of burnout and isolation because of outpatient needs and limited community support. [11][12][13][14] Several analyses 7,15,16 have concluded that goals of care of patients receiving DT are often undefined. Many patients either have inadequate advance directives that do not address potential problems (such as worsening comorbid conditions, complications, and worsening QOL) or simply lack advance care documents.…”
Section: Methodsmentioning
confidence: 99%
“…Many patients either have inadequate advance directives that do not address potential problems (such as worsening comorbid conditions, complications, and worsening QOL) or simply lack advance care documents. 7,16,17 Without clearly defined goals and/or explicit advance directives, DT may merely maintain circulation in a moribund patient, a situation referred to as "destination nowhere." 18 Also, protocols and processes regarding LVAD management and comfort at the end of life are often lacking 7,17 ; hence, ethical quandaries (eg, withdrawal of device support) may arise.…”
Section: Methodsmentioning
confidence: 99%
“…As VAD placement is discussed with patient and family, end of life issues must be addressed, not only because of the seriousness of the current illness and the potential mortality of the operation but also because the treatment equates to mobile life support [52 • ]. While VADs have repeatedly been shown to increase quality of life, the possibility of a patient eventually asking to withdraw this life-prolonging care has been seen in multiple studies to be approximately 20 % [51,53]. While some believe that once implanted a VAD becomes one with the patient and deactivating it amounts to euthanasia, most ethicists agree that deactivation of the VAD equates to withdrawal of life support and the terminal insult is that of heart failure, not the deactivation of the VAD by the physician [54].…”
Section: Ethical Concernsmentioning
confidence: 99%